A narrative review on haptic devices: relating the physiology and psychophysical properties of the hand to devices for rehabilitation in central nervous system disorders. (May 2013) - Demain, Sara; Metcalf, Cheryl D.; Merrett, Geoff V.; Zheng, Deyi; Cunningham, Sarah
<x xml:space="preserve">Abstract</x> Purpose: This article provides rehabilitation professionals and engineers with a theoretical and pragmatic rationale for the inclusion of haptic feedback in the rehabilitation of central nervous system disorders affecting the hand. Method: A narrative review of haptic devices used in sensorimotor hand rehabilitation was undertaken. Presented papers were selected to outline and clarify the underlying somatosensory mechanisms underpinning these technologies and provide exemplars of the evidence to date. Results: Haptic devices provide kinaesthetic and/or tactile stimulation. Kinaesthetic haptics are beginning to be incorporated in central nervous system rehabilitation; however, there has been limited development of tactile haptics. Clinical research in haptic rehabilitation of the hand is embryonic but initial findings indicate potential clinical benefit. Conclusions: Haptic rehabilitation offers the potential to advance sensorimotor hand rehabilitation but both scientific and pragmatic developments are needed to ensure that its potential is realized.